Role of DLC2 and RhoA/ROCK pathway in formalin induced inflammatory pain in mice. (14th September 2019) - Wong, Stanley Sau Ching; Lee, Un Man; Wang, Xiao-Min; Chung, Sookja Kim; Cheung, Chi Wai
Highlights: Investigated a novel role of DLC2 in regulating inflammatory pain. DLC2 deficiency (DLC2 −/− ) mice showed increased mechanical allodynia and thermal hyperalgesia. RhoA or ROCK inhibitor attenuated nociceptive hypersensitivity in DLC2 −/− mice. The DLC2/RhoA/ROCK2 cascade may be a potential therapeutic target for inflammatory pain. Abstract: Deficiency of deleted in liver cancer 2 (DLC2), a novel domain to inhibit RhoA activity, plays an important role in inflammatory pain. However, the underlying mechanisms remain unclear. This study investigated the role of DLC2 and its downstream cascade of RhoA/ROCK in formalin-induced inflammatory pain using DLC2-knockout (DLC2 −/− ) mice and compared them with DLC2 wild-type (DLC2 +/+ ) mice. Mechanical allodynia and thermal hyperalgesia were evaluated using von Frey filament aesthesiometer and Hargreaves test, respectively. The spinal cord dorsal horn (L3-L5) was selected for molecular and cellular identification by Western blot and immunofluorescence. DLC2 −/− mice showed increased mechanical allodynia and thermal hyperalgesia. Expression of ROCK1, ROCK2 and IL-1β was significantly higher in DLC2 −/− mice. Intrathecal administration of RhoA inhibitor (C3 exoenzyme) or ROCK inhibitor (Y27632) significantly attenuated formalin-induced inflammatory hyperalgesia in DLC2 −/− mice. ROCK2 and IL-1β expression were reduced by C3 exoenzyme or Y27632. Spinal p38 activation was also inhibited by C3 exoenzyme or Y27632. Double-labelling immunofluorescence demonstrated co-localization of DLC2 with spinal dorsal microglia. The number of activated microglia in the spinal dorsal horn was significantly higher in DLC2 −/− mice, but was reduced by Y27632. These findings indicate that DLC2 deficiency increased formalin-induced inflammatory hyperalgesia through regulating RhoA/ROCK2, and IL-1β may be a downstream effector. Our results also suggest that RhoA/ROCK enhanced p38 activation plays an important role in formalin-induced inflammatory pain. The finding that DLC2 attenuated inflammatory pain through inhibiting RhoA/ROCK2 suggests that the DLC2/RhoA/ROCK2/p38/IL-β pathway may be a potential therapeutic target to reduce inflammatory pain.